Development of exhaustion for high-performance coaches in association with workload and motivation: A person-centered approach. (January 2016) - Bentzen, Marte; Lemyre, Pierre-Nicolas; Kenttä, Göran
Abstract: Objectives: The aim of the current study was twofold. First, to explore whether there were different trajectories of exhaustion among high-performance coaches over the course of a competitive season. Then, to investigate whether workload-related variables and motivational regulations were associated with exhaustion class membership. Methods and design: 299 high-performance coaches responded to an online survey at the start, middle, and end of a competitive season, assessing exhaustion, workload, work home interference (WHI), recovery, and motivational regulations. Latent class growth analyses were used to identify different trajectories of perceived exhaustion. Further, multinomial logistic regression examined class associations for workload-related variables and motivational regulations at the start and at the end of competitive season. Results: Four different trajectories of perceived exhaustion among coaches were identified, termed respectively " High " (10%), " Increase " (15%), " Decrease " (4%) and " Low " (71%). Higher levels of workload and WHI were associated to classes with higher levels of exhaustion. Higher levels of recovery, and intrinsic and identified regulations were associated to classes with lower levels of exhaustion. Adaptive and maladaptive profiles were identified. Conclusions: Different trajectories of exhaustion among high-performance coaches over the course of a competitive season were found. A maladaptive profile was associated with higher perceived workload and WHI, as well as lower levels of recovery, intrinsic and identified regulations, when compared to the adaptive profile. Highlights: Latent class growth analyses were used to examine for different trajectories of exhaustion among high-performance coaches. Four different exhaustion trajectories were identified; "High" (10%), "Increase" (15%), "Decrease" (4%) and "Low" (71%). The trajectories were associated to differentiated levels of workload, WHI, recovery, intrinsic and identified regulation. A maladaptive profile corresponded to higher workload and WHI, and lower recovery, intrinsic, and identified regulation.